2018
DOI: 10.1248/bpb.b18-00222
|View full text |Cite
|
Sign up to set email alerts
|

Generation of the Adenovirus Vector-Mediated CRISPR/Cpf1 System and the Application for Primary Human Hepatocytes Prepared from Humanized Mice with Chimeric Liver

Abstract: The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas) 9 system is now widely used as a genome editing tool. CRISPR-associated endonuclease in Prevotella and Francisella 1 (Cpf1) is a recently discovered Cas endonuclease that is designable and highly specific with efficiencies comparable to those of Cas9. Here we generated the adenovirus (Ad) vector carrying an Acidaminococcus sp. Cpf1 (AsCpf1) expression cassette (Ad-AsCpf1) for the first time. Ad-AsCpf1 was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Other approaches will edit transgenic silkworms infected with bacterial diseases, fungal diseases and Nosema bombycis according to the characteristics of different silkworm diseases. Currently, the CRISPR family has identified gene editing systems including CRISPR/CPF1 and CRISPR/Cas13, that could edit the DNA, RNA or both DNA and RNA sequences [35,36]. CRISPR/CPF1 and CRISPR/Cas13 systems have smaller nuclease proteins and have more RNA target sequences and lower off-target efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches will edit transgenic silkworms infected with bacterial diseases, fungal diseases and Nosema bombycis according to the characteristics of different silkworm diseases. Currently, the CRISPR family has identified gene editing systems including CRISPR/CPF1 and CRISPR/Cas13, that could edit the DNA, RNA or both DNA and RNA sequences [35,36]. CRISPR/CPF1 and CRISPR/Cas13 systems have smaller nuclease proteins and have more RNA target sequences and lower off-target efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the Cas9 induced blunt end cuts, it creates cuts in a zig zag manner along with requiring a small gRNA [29,30]. Tsukamoto et al have observed reduced mutation rates and enhanced viability during manipulation of human hepatocytes using CRISPR/Cpf1 system [31]. Similarly, other authors have also mentioned advantages in terms of speed, efficiency, specificity and multiplexing option in possible real-time clinical deployment of genome editing [32].…”
Section: Table-1: Various Modifications and Improvements Attempted Over Last Few Years In Crispr/cas Technology A Modified Cas/nucleases mentioning
confidence: 99%
“…The most common physical delivery techniques include microinjection and electroporation. Viral delivery vectors include retrovirus, lentivirus, adeno-associated virus (AAV), and adenovirus (Ad) vectors [43]. Viral vectors are especially appropriate vehicles for in vivo works, most commonly used for CRISPR system delivery.…”
Section: Cpf1 Delivery Strategiesmentioning
confidence: 99%
“…Recently, there was a generation of Ad vector-mediated CRISPR/Cpf1 system which proved to be valuable in genome editing in primary human hepatocytes. Despite the lower immunogenicity of AAV vectors than Ad vectors and their more safety for therapeutic applications in humans, AAV vectors have smaller packaging capacity than Ad vectors [43].…”
Section: Cpf1 Delivery Strategiesmentioning
confidence: 99%
See 1 more Smart Citation